Empowerment of North American Indian girls : ritual expressions at puberty - Markstrom, Carol A. (Book collections on Project MUSE., 2008)
Empowerment of North American Indian Girls is an examination of coming-of-age-ceremonies for American Indian girls past and present, featuring an in-depth look at Native ideas about human development and puberty. Many North American Indian cultures regard the transition from childhood to adulthood as a pivotal and potentially vulnerable phase of life and have accordingly devised coming-of-age rituals to affirm traditional values and community support for its members. Such rituals are a positive and enabling social force in many modern Native communities whose younger generations are wrestling with substance abuse, mental health problems, suicide, and school dropout.